1991
DOI: 10.1210/endo-128-1-388
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Human Chorionic Gonadotropin/Luteinizing Hormone Receptor Down-Regulation Involves Decreased Levels of Receptor Messenger Ribonucleic Acid*

Abstract: Injection of pseudopregnant rats with pharmacological doses of hCG leads to a characteristic decrease in LH/hCG binding by the isolated luteal cells. The steady state levels of LH/hCG receptor mRNA were determined in rat ovaries during hCG-induced down-regulation of the receptor. Northern blots were performed using a 20-mer probe corresponding to a guanine cytosine-rich carboxyl-terminal untranslated region of the LH/hCG receptor cDNA. The hybridization of the probe to LH/hCG receptor mRNA was highly specific,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 11 publications
5
68
0
Order By: Relevance
“…This was followed by a gradual recovery to control levels by 72 h, as shown in the solution hybridization analysis data presented in Fig 1. The loss of mRNA was rather unexpected, since the decrease of cell surface receptor expression was thought to occur through rapid internalization of the ligand-bound receptor. In the control samples an increase in LHR mRNA expression was seen during the time-course of the experiment, since our previous studies have shown that in pseudopregnant rat ovary the expression of LHR mRNA increased up to day 8 (Hoffman, et al 1991). The in situ hybridization pattern confirmed the Northern blot data and further suggested that the same corpora lutea that were depleted of the receptor mRNA reacquired the receptor (Peegel et al, 1994).…”
Section: Lh Receptor Mrna Expression During Ligand-induced Down-regulsupporting
confidence: 74%
See 3 more Smart Citations
“…This was followed by a gradual recovery to control levels by 72 h, as shown in the solution hybridization analysis data presented in Fig 1. The loss of mRNA was rather unexpected, since the decrease of cell surface receptor expression was thought to occur through rapid internalization of the ligand-bound receptor. In the control samples an increase in LHR mRNA expression was seen during the time-course of the experiment, since our previous studies have shown that in pseudopregnant rat ovary the expression of LHR mRNA increased up to day 8 (Hoffman, et al 1991). The in situ hybridization pattern confirmed the Northern blot data and further suggested that the same corpora lutea that were depleted of the receptor mRNA reacquired the receptor (Peegel et al, 1994).…”
Section: Lh Receptor Mrna Expression During Ligand-induced Down-regulsupporting
confidence: 74%
“…The in situ hybridization pattern confirmed the Northern blot data and further suggested that the same corpora lutea that were depleted of the receptor mRNA reacquired the receptor (Peegel et al, 1994). The loss of LH receptor mRNA was specific, as other LH/hCG responsive mRNAs such as Cytochrome p450scc remained at a level significantly higher than the saline treated controls (Hoffman, et al 1991). The loss of LH receptor mRNA occured through post-transcriptional mechanisms as the transcription rate, determined by nuclear run on assays, remained identical in hCG treated group compared to the control.…”
Section: Lh Receptor Mrna Expression During Ligand-induced Down-regulsupporting
confidence: 70%
See 2 more Smart Citations
“…The cell surface expression of LHR varies during different stages of the ovarian cycle. Its expression in granulosa cells and luteal cells is greatly decreased by an endogenous preovulatory LH surge or by the administration of a pharmacological dose of human chorionic gonadotropin (hCG), a placental counterpart of LH (5)(6)(7)(8). We have shown that the decline in cell surface LHR expression seen after hCG administration is paralleled by a specific loss of all four LHR mRNA transcripts (6.7, 4.4, 2.6, and 1.8 kb) in the ovary (9).…”
mentioning
confidence: 99%